Interação coordenador pedagógico Professores: um estudo sobre leitura colaborativa - Previattelli, Wania Maria (2016)
The present work is a research that aimed to analyze to what extent the pedagogical coordinators, subject of training reading teaching have appropriated the principles of collaborative/shared reading and as forwarded this discussion with teachers. The critical incident technique were used for data collection with the pedagogical coordinators of a Directorate of Public Education in the interior of São Paulo State. As theoretical referents were used that deal with authors of such training as Délia Lerner, Isabel Solé, Frank Smith e Ângela Kleiman. The analysis of the responses identified that: there are different understandings about the purpose of the shared reading and to whom; the applicant's idea of "help the professor" in forwards proposed by them, yet prescriptive character-based. The data allowed the analysis of the interactions between the pedagogical coordinators with their teachers and their consequences on pedagogical practice